Incidence of Postoperative Residual Neuromuscular Blockade at the Postanesthesia Care Unit Following General Anesthesia - Sarinya Chanthawong; Thidamas Apithambundit; Netinai Chaimala; Sangmukda Saras; Thanat Yotepanya; Saranyoo Nonphiaraj (Siriraj Medical Journal, 2025)
Objective: This study aimed to investigate residual neuromuscular blockade (RNMB) and respiratory adverse events and identify risk factors for RNMB.